TI_GERICHTE 12.2011.87 vom 25. Juli 2011 , Azione di inesistenza del debito - sospensione provvisoria dell'esecuzione - TI Tribunale d'appello (2011)
Azione di inesistenza del debito - sospensione provvisoria dell'esecuzione